∫ − 2 2 1 + 2 x 1 + x 2 d x = b a
The equation above holds for coprime positive integers a and b .
Find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice!!! (+1)
Relevant wiki: Integration Tricks
We substitute the variable x with − x and add the resulting integral to the original integral to get
2 I = ∫ − 2 2 1 + 2 x 1 + x 2 d x + ∫ 2 − 2 − 1 + 2 − x 1 + x 2 d x
= ∫ − 2 2 1 + 2 x 1 + x 2 + 1 + 2 − x 1 + x 2 d x
= ∫ − 2 2 1 + 2 x 1 + x 2 + 1 + 2 − x 1 + x 2 ⋅ 2 x 2 x d x
= ∫ − 2 2 1 + 2 x ( 1 + x 2 ) 2 x + 1 + 2 x 1 + x 2 d x
∫ − 2 2 1 + 2 x ( 1 + x 2 ) ⋅ ( 1 + 2 x ) d x
∫ − 2 2 1 + x 2 d x = 4 + 3 1 6 = 3 2 8
Thus, I = 3 1 4
Note that more generally, for even functions f , ∫ − a a 1 + b x f ( x ) d x = 2 1 ∫ − a a f ( x ) d x .
Nicely done.
What I would have done is to show that 1 + 2 x 1 + 1 + 2 − x 1 = 1 is true first, then the remaining working becomes much simpler, because there are no fractions involved anymore!
Log in to reply
Ah yes, I noticed with Chew-Seong's concise solution. Thank you, Pi!
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Integration Tricks
I = ∫ − 2 2 1 + 2 x 1 + x 2 d x = 2 1 ∫ − 2 2 1 + 2 x 1 + x 2 + 1 + 2 − x 1 + x 2 d x = 2 1 ∫ − 2 2 ( 1 + x 2 ) ( 1 + 2 x 1 + 2 x + 1 2 x ) d x = 2 1 ∫ − 2 2 ( 1 + x 2 ) d x = ∫ 0 2 ( 1 + x 2 ) d x = x + 3 x 3 ∣ ∣ ∣ ∣ 0 2 = 2 + 3 8 = 3 1 4 Using identity ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x Note that 1 + x 2 is even.
⟹ a + b = 1 4 + 3 = 1 7